If you build it, will they come? Spawning habitat remediation for sturgeon. (19th December 2017) - McAdam, S. O.; Crossman, J. A.; Williamson, C.; St‐Onge, I.; Dion, R.; Manny, B. A.; Gessner, J.
Summary: Habitat loss is a widely recognized contributor to global declines in sturgeon populations yet habitat remediation has been limited for this highly endangered group of fish. In support of future sturgeon restoration efforts, this review examines habitat remediation needs and uncertainties. Consideration of the bio‐spatial scale of remediation identified needs ranging from local to the whole river scale. Additionally, the context of remediation ranges from reintroducing sturgeon to habitats where they have been extirpated to conservation of currently functional habitat. While multiple remediation scales and contexts are discussed, the focus on spawning and early rearing habitat and associated biological and physical monitoring reflects the range of current projects and the importance of early rearing habitats. Four case studies are presented that examine four distinct remediation contexts (mitigation, rejuvenation, re‐creation, repatriation) and three bio‐spatial scales (whole river, spawning reach, spawning location) under which remediation has been attempted. Evaluation of existing remediation works indicates that many show limited long‐term success, which is most often a response to substrate infilling in remediated habitats. Material presented in this review will help align sturgeon research and monitoring approaches in support of effective remediation. The limited number of remediation projects to‐date attests to the importance of learning from existing projects and cross‐species comparisons, to maximize the effectiveness of future restoration efforts.